KETERLIBATAN PESERTA DIDIK DALAM PEKERJAAN ORANG TUA DI MIS WORA KEC. WERA KAB. BIMA - Roswati; Usman, Syahruddin; Rahman, Ulfiani; Muhammad Nur Korompot (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research aims to obtain an overview of the involvement of MIS Wora Wera students in their parents' work. This type of research is quantitative research that uses quantitative analysis methods. Data collection uses research instruments, data analysis is quantitative or statistical. The type of research is correlation which is adjusted to the researcher's objectives by connecting causality and correlation between the independent variable of student involvement in their parents' work and the dependent variables of interest in learning and PAI learning outcomes and character. From the results of descriptive statistical analysis, it was found that the average learning outcomes for PAI subjects and character for 20 class III students were 76.4; 77.25, and 77.4 and standard deviation of 3.32; 4; and 3.3, in class IV with a total of 20 students, the average learning result for PAI and character subjects reached 77; 77.5; and 76 with a standard deviation of 7.07; 6.25; and 4,242. In class V with 22 students, the average learning result for PAI and character subjects was 78.59; 79.05; and 78.82 with a standard deviation of 6.25; 6.67; and 6.48. The correlation value (r_xy) of students' involvement in their parents' work is 0.875 at a significance level of 5%, obtained by r_table of 0.250, thus r_count > r_tabel, this means that H_0 is rejected, which means there is a correlation with students' involvement in their parents' work. So it can be concluded that there is a significant relationship between the involvement of students in their parents'